Analysis of the Potential of Renewable Energy in South Sulawesi as Power Electrical Needs - Mochammad Apriyadi Hadi Sirad (Universitas Muhammadiyah Yogyakarta, 2017)
Abstract - The use of electric energy in Indonesia continue to experience the increase, especially in South Sulawesi. Electric power demand will grow by achieving average 6.5% per year until the year 2022. In this case the researchers refer to the law 30 of 2007 about energy. Renewable energy potential which exists in South Sulawesi very potential so that needs to be held for research potential. This study was carried out in several districts with priority the potential of renewable energy sources is micro hydro energy, solar energy. Research results show that the potential of renewable energy, solar energy has the greatest potential, namely Sun shines of 337 mwe, with the highest temperature i.e. 95.5 ° c, Ph = 8-9 that is located in the Selayar potentially to develop solar power plant where the average energy of the solar electricity produced amounted to 2,450 units.